Consequences of oral antithrombotic use in patients with chronic kidney disease. Issue 6 (24th June 2021) - Laville, Solène M.; Lambert, Oriane; Hamroun, Aghiles; Metzger, Marie; Jacquelinet, Christian; Laville, Maurice; Frimat, Luc; Fouque, Denis; Combe, Christian; Ayav, Carole; Pecoits‐Filho, Roberto; Stengel, Bénédicte; et al.
Abstract: We assessed the risks of bleeding, acute kidney injury (AKI), and kidney failure associated with the prescription of antithrombotic agents (oral anticoagulants and/or antiplatelet agents) in patients with moderate‐to‐advanced chronic kidney disease (CKD). CKD‐REIN is a prospective cohort of 3022 nephrology outpatients with CKD stages 2–5 at baseline. We used cause‐specific Cox proportional hazard models to estimate hazard ratios (HRs) for bleeding (identified through hospitalizations), AKI, and kidney failure. Prescriptions of oral antithrombotics were treated as time‐dependent variables. At baseline, 339 (11%) patients (65% men; 69 [60–76] years) were prescribed oral anticoagulants only, 1095 (36%) antiplatelets only, and 101 (3%) both type of oral antithrombotics. Over a median (interquartile range [IQR]) follow‐up period of 3.0 (IQR, 2.8–3.1) years, 152 patients experienced a bleeding event, 414 patients experienced an episode of AKI, and 270 experienced kidney failure. The adjusted HRs (95% confidence interval [95% CI]) for bleeding associated with prescriptions of antiplatelets only, oral anticoagulants only, and antiplatelet + oral anticoagulant were, respectively, 0.74 (95% CI, 0.46–1.19), 2.38 (95% CI, 1.45–3.89), and 3.96 (95% CI, 2.20–7.12). An increased risk of AKI risk was associated with the prescription of oral anticoagulants (adjusted HR, 1.90, 95% CI, 1.47–2.45) but not the prescription of antiplatelets (HR, 1.24, 95% CI, 0.98–1.56). Kidney failure was not associated with the prescription of oral antithrombotics of any type. This study confirms the high risk of AKI associated with oral anticoagulants prescription in patients with CKD and also highlights the potential aggravating effect of combining vitamin K antagonist (VKA) and antiplatelets on the risk of bleeding.